PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN RUMAH DI GOLDEN CITY RESIDENCE - Kevin Kevin; Inda Sukati (SCIENTIA JOURNAL, 2026)
This study aims to analyze the influence of product quality and brand image on the decision to purchase houses at Golden City Residence Batam. The research background is based on the importance of the housing sector as a primary necessity as well as a long-term investment, along with the increasing competition among developers in offering high-quality residences with strong brand images. This study employs a quantitative method with a causal approach. The research population consists of 137 consumers who have purchased houses at Golden City Residence, all of whom were included as the research sample using a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed with the assistance of SPSS software through validity and reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests. The hypotheses in this study include the presumed influence of product quality on purchasing decisions, the influence of brand image on purchasing decisions, and the simultaneous influence of product quality and brand image on purchasing decisions. Keywords: Brand Image, Golden City Residence, Housing, Product Quality, Purchasing Decision